Students Mathematical Literacy ability Judging from the Adversity Quotient and Gender in Problem Based Learning Assisted Edmodo - Hairunnisah, Hairunnisah; Suyitno, Hardi; Hidayah, Isti (Universitas Negeri Semarang, 2019)
This study aims to determine the effectiveness of PBL assisted by Edmodo on students' mathematical literacy skills and find the mathematical literacy patterns of students reviewed adversity quotient (AQ) and Gender. This study uses a mixed method with embedded concurent design. Sample of this study were 8th grade students of SMP IT Insan Cendekia 2017/2018 school year. The results showed that students with Edmodo-assisted PBL learning achieved better and better than students on PBL. The pattern of literacy ability of male climber type students is able to master the aspects of communication, mathematics, representation, reasoning and giving reasons, designing strategies for problem solving, use of symbols, formal language, practice and operations. Climber type female students are able to master aspects of communication, mathematics, representation, reasoning and giving reasons, designing problem solving strategies. Camper type male students master the aspects of communication, mathematics, representation, reasoning and giving reasons, designing strategies to solve problems, use symbols, formal language, practice and operate well. Camper type female students master aspects of communication, reasoning and giving reasons and designing problem solving strategies. Quitter type students are only able to master the aspects of communication, reasoning and giving reasons. Quitter type female students master aspects of communication, representation, reasoning and giving reasons.